Encyclopedia of Neuroscience - Binder, Marc D. (Springer, 2011)
Comprehensive: includes more than 10,000 entries with keynotes, in-depth essays and reviews on 43 topic fields Visually sumptuous with some 1,000 full-color illustrations Intelligently structured, accessible and user-friendly: A-Z format, clear, concise language and uniform essay structure provides easy access to content Authoritative, with more than 1,000 expert contributors, under the guidance of more than 40 field editors Available both in print and as a fully searchable and hyperlinked electronic online edition, making it as convenient as it is exhaustive